Preparation of Biocompatible, UV-Cured Fumarated Poly(ether-ester)-Based Tissue-Engineering Hydrogels - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2011)
The aim of this study was to develop biodegradable, photo-polymerizable in situ gel-forming systems prepared from a fumaric acid monoethyl ester (FAME) modified poly(lactide-co-glycolide) (PLGA) copolymer. By reacting lactide and glycolide in the presence of stannous octoate as a catalyst and 2-ethyl, 2-hydroxymethyl 1,3-propanediol as an initiator, hydroxyl terminated branched PLGA was synthesized. Afterwards, at room temperature hydroxyl terminated branched PLGA was reacted with fumaric acid monoethyl ester (FAME). N,N'-dicyclohexylcarbodiimide and triethylamine were used as a coupling agent and catalyst, respectively. The gel percentage, equilibrium mass swelling, degradation profile and polymerization kinetics of the hydrogels were investigated. All of the results were influenced by the amount of FAME modified PLGA co-polymer. Biocompatibility of the hydrogels was examined by using MTT cytotoxicity assay. According to the results, hydrogels are biocompatible and cell viability percentage depends on the amount of PLGA co-polymer. While the amount was 15% in hydrogel composition, cell viability was 100%, but after increasing the PLGA co-polymer amount to 30% the viability reduced to 78%. (C) Koninklijke Brill NV, Leiden, 2011
Keywords: Tissue engineering; osteoblast; PLGA; biodegradation; hydrogel; UV; CALCIUM-PHOSPHATE; SCAFFOLDS; DEGRADATION; COPOLYMER; NETWORKS; CARTILAGE; KINETICS; DELIVERY; IMPACT